A vesicular porous carbon active negative electrode material and a preparation method and application thereof

CN122897402APending Publication Date: 2026-10-13NANTONG BOAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410804369.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的在于为了克服现有技术的不足而提供一种囊泡状多孔碳活性负极材料及其制备方法和应用,以解决传统模板法存在的产物形状和尺寸单一、成本高、工艺复杂、环境污染,化学活化法对设备和环境造成破坏等问题

Benefits of technology

[0019]1)本发明采用液态模板协同燃烧活化的固态合成方法获得具有囊泡状独特形貌和分级多孔结构的氮氧硼三掺杂囊泡状多孔碳活性负极材料,所述制备工艺简单,克服了传统模板法与化学活化法的弊端;且本发明利用乙二胺四乙酸四钠、硼酸铵、硝酸钾为原料,以水为溶剂,所用原料均具有无毒,低成本且易获得的优点;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897402A_ABST
    Figure CN122897402A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of porous carbon material, and provides a vesicular porous carbon active negative electrode material, a preparation method and application thereof.The preparation method comprises the following steps: mixing tetrasodium ethylenediaminetetraacetate, a boron source, a nitrate and a solvent, and then sequentially performing freeze-drying and carbonization to obtain the vesicular porous carbon active negative electrode material.The vesicular porous carbon active negative electrode material with unique vesicular morphology and hierarchical porous structure and doped with nitrogen, oxygen and boron is obtained by using a liquid template and a solid-state synthesis method of combustion activation, the preparation process is simple, and the drawbacks of traditional template methods and chemical activation methods are overcome;the vesicular porous carbon active negative electrode material has a vesicular spherical shell structure connected with each other, which is beneficial to improving the transmission rate of ions and electrons and buffering the strain caused by Na + storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous carbon materials technology, and in particular to a vesicle-like porous carbon active anode material, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries (SIBs) are considered the most promising alternative power source for next-generation renewable energy storage systems because sodium (Na) is present in the Earth's crust at 2.3 wt%, far exceeding the abundance of lithium (0.0017 wt%) and potassium (1.5 wt%). However, sodium... + The radius is Greater than Li + radius This leads to severe volume changes and slow diffusion kinetics in the electrode material, posing a significant challenge to its structural stability, rate performance, and cycle life. Among various anode materials for SIBs, hard carbon, with its numerous defects, graphitic crystallites, and porosity, is the most promising anode material for commercial SIBs. However, the Na+ in highly graphitized hard carbon... + Storage behavior follows an "adsorption-intercalation" mechanism, resulting in its reversible specific capacity primarily originating from the plateau region (Na). + (Intercalated between graphite layers). Although hard carbon can achieve a specific capacity of around 300 mAh / g at low current densities, the specific capacity contribution from the plateau region is minimal at high current densities due to its high sensitivity to polarization. Therefore, hard carbon exhibits poor rate performance at high current densities. Furthermore, hard carbon typically requires calcination of precursors at very high temperatures, resulting in low yields. These factors limit the practical applications of hard carbon.

[0003] Porous carbon possesses a robust framework, high heteroatom content, abundant pores and defects, and good electrical conductivity, making it suitable for use with Na. + The transmission provides more channels, shortening the Na + Diffusion distance, improving the ability to deal with Na + Adsorption capacity of Na, alleviate Na +The volume expansion caused by embedding is significant. Therefore, the specific capacity contribution of the porous carbon slope region is the largest, resulting in high rate performance and cycle stability. Studies have shown that an effective strategy to improve the sodium storage performance of porous carbon is to adjust its morphology and chemical composition. Among the many methods for preparing porous carbon, template methods and chemical activation methods are considered relatively ideal because template methods can control morphology and pore size distribution, while chemical activation methods can construct hierarchical porous structures. However, template methods suffer from problems such as limited product shape and size, high cost, complex processes, and environmental pollution; chemical activation methods (such as KOH and H3PO4 activation) can damage equipment and the environment, thus limiting the practical application of these two methods. Furthermore, the porous carbon prepared by the above methods exhibits poor stability and rate performance in ester-based sodium-ion batteries. To overcome this limitation on porous carbon sodium-ion batteries, ether-based electrolytes are often used to replace traditional ester-based electrolytes, and they exhibit superior SIB electrochemical performance in various negative electrodes such as graphite, metal sulfides, and transition metal oxides. Compared to ester-based electrolytes, ether-based electrolytes can react with Na+. + The formation of weak coordination accelerates the kinetic process and promotes Na + Transport. Ether-based electrolytes enable rapid Na+ transfer in SIBs. + Storage kinetics and highly reversible sodium insertion / deintercalation reactions. However, replacing ester-based electrolytes with ether-based electrolytes cannot fundamentally solve the problems of low initial coulombic efficiency, small specific capacity, poor rate performance, and short cycle life of current porous carbon anode materials in ester-based electrolytes.

[0004] Therefore, there is an urgent need to develop a porous carbon active anode material that can flexibly control the morphology and chemical composition of porous carbon, overcome the shortcomings of traditional template methods and chemical activation methods, and improve the electrochemical performance of porous carbon materials in sodium-ion batteries. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art by providing a vesicle-like porous carbon active anode material, its preparation method, and its application, so as to solve the problems of the traditional template method, such as the product shape and size being limited, high cost, complex process, and environmental pollution, and the chemical activation method causing damage to equipment and the environment.

[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0007] This invention provides a method for preparing a vesicle-like porous carbon active anode material, comprising the following steps:

[0008] Tetrasodium ethylenediaminetetraacetate, boron source, nitrate and solvent were mixed and then freeze-dried and carbonized sequentially to obtain a vesicular porous carbon active anode material.

[0009] Preferably, the boron source is ammonium borate.

[0010] Preferably, the nitrate is potassium nitrate and the solvent is water.

[0011] Preferably, the molar ratio of the tetrasodium ethylenediaminetetraacetate, the boron source, and the nitrate is 1:2.2-3.8:1-2, and the volume-to-mass ratio of the solvent to the tetrasodium ethylenediaminetetraacetate is 100-300 mL:1.5-5.5 g.

[0012] Preferably, the mixing is carried out under stirring conditions, with a mixing rate of 200–800 r / min and a mixing time of 6–15 h.

[0013] Preferably, the freeze-drying temperature is -60 to -50°C, and the freeze-drying time is 48 to 64 hours.

[0014] Preferably, the carbonization is carried out in a protective gas atmosphere, the protective gas being argon and / or nitrogen, the flow rate of the protective gas being 40–100 mL / min; the carbonization temperature being 800–1200 °C; the carbonization time being 1–5 h; and the heating rate to the carbonization temperature being 4–8 °C / min.

[0015] Preferably, after carbonization, the carbonization product is post-processed to obtain a vesicular porous carbon active negative electrode material. The post-processing includes sequential removal of impurities, separation, washing, and drying. The drying temperature is 70-120°C.

[0016] The present invention also provides a vesicle-like porous carbon active anode material prepared by the preparation method described above.

[0017] The present invention also provides the application of the aforementioned vesicular porous carbon active anode material in sodium-ion batteries.

[0018] The beneficial effects of this invention include the following:

[0019] 1) This invention employs a solid-state synthesis method with liquid template synergistic combustion activation to obtain nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material with a unique vesicular morphology and hierarchical porous structure. The preparation process is simple and overcomes the drawbacks of traditional template methods and chemical activation methods. Furthermore, this invention uses tetrasodium ethylenediaminetetraacetate, ammonium borate, and potassium nitrate as raw materials and water as a solvent. All raw materials used have the advantages of being non-toxic, low-cost, and readily available.

[0020] 2) The vesicular porous carbon active negative electrode material prepared by this invention has an interconnected vesicular spherical shell structure, which is beneficial to improving the transport rate of ions and electrons and buffering Na. + Strain caused by storage;

[0021] 3) In the vesicular porous carbon active anode material prepared by this invention, the synergistic effect of N, O, and B triple doping is beneficial to increasing defects and widening the carbon layer spacing, thereby promoting Na + Adsorption and intercalation; high mesopore content is beneficial for Na + The transmission;

[0022] 4) The hybrid network structure composed of alternating disordered and ordered regions in the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material prepared by this invention achieves a balance between high conductivity and high electrochemical activity.

[0023] 5) The nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material prepared by this invention improves or solves the problems of small reversible capacity, low initial coulombic efficiency, and poor cycle stability of porous carbon anodes, providing more opportunities for exploring advanced electrode materials. Attached Figure Description

[0024] Figure 1 SEM image of the nitrogen, oxygen, and boron triple-doped vesicle-like porous carbon active anode material of Example 1;

[0025] Figure 2 SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material of Comparative Example 1;

[0026] Figure 3 This is a SEM image of the nitrogen-oxygen-doped porous carbon active anode material in Comparative Example 2.

[0027] Figure 4 This is a SEM image of the nitrogen-oxygen-doped porous carbon active anode material in Comparative Example 3.

[0028] Figure 5 SEM image of the nitrogen, oxygen, and boron triple-doped porous carbon active anode material in Comparative Example 4;

[0029] Figure 6 SEM image of nitrogen-oxygen doped porous carbon active anode material in Comparative Example 5;

[0030] Figure 7 SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material of Comparative Example 6;

[0031] Figure 8 SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material of Comparative Example 7;

[0032] Figure 9 SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material of Comparative Example 8;

[0033] Figure 10 SEM image of the nitrogen, oxygen, and boron triple-doped porous carbon active anode material of Comparative Example 9;

[0034] Figure 11 X-ray diffraction patterns of porous carbon active anode materials in Examples 1 and 1-3;

[0035] Figure 12 The X-ray diffraction patterns of the porous carbon active anode materials in Comparative Examples 4–9 are shown below.

[0036] Figure 13 Comparative graphs show the charge-discharge performance of porous carbon active anode materials used as anodes in sodium-ion batteries at a current density of 0.05 A / g in ether-based electrolytes, as shown in Example 1 and Comparative Examples 1-3.

[0037] Figure 14 Comparative graphs show the charge-discharge performance of porous carbon active anode materials (Examples 4-9) as anodes in sodium-ion batteries at a current density of 0.05 A / g in ether-based electrolytes.

[0038] Figure 15 This is a comparison chart showing the rate performance of porous carbon active anode materials used as anodes in sodium-ion batteries in ether-based electrolytes, as shown in Example 1 and Comparative Examples 1-3.

[0039] Figure 16 Comparison of rate performance of porous carbon active anode materials (Examples 4-9) as anodes in sodium-ion batteries in ether-based electrolytes.

[0040] Figure 17 The impedance comparison diagrams are shown for porous carbon active anode materials of Examples 1 and Comparative Examples 1-3 as anodes in sodium-ion batteries in ether-based electrolytes.

[0041] Figure 18 The impedance comparison diagrams of porous carbon active anode materials (Comparative Examples 4-9) as anodes in sodium-ion batteries in ether-based electrolytes are shown.

[0042] Figure 19 The graph shows the specific capacity and cycling performance of EBNK in Example 1 under different currents in an ether-based electrolyte.

[0043] Figure 20 The graph shows a comparison of the charge-discharge curves of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material of Example 1 as a sodium-ion battery anode in ether-based and ester-based electrolytes at a current density of 0.05 A / g.

[0044] Figure 21 The graph shows a comparison of the rate performance of the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material of Example 1 as an anode in sodium-ion batteries in ether-based electrolytes and ester-based electrolytes.

[0045] Figure 22The figure shows the cyclic voltammetry curve of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material of Example 1 as a sodium-ion battery anode in an ether-based electrolyte at 0.2 mV / s.

[0046] Figure 23 The figure shows the cyclic voltammetry curve of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material of Example 1 as a sodium-ion battery anode in an ester-based electrolyte at 0.2 mV / s.

[0047] Figure 24 The graph shows a comparison of the long-cycle performance of the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material of Example 1 as an anode in a sodium-ion battery at a current density of 5A / g in ether-based electrolyte and ester-based electrolyte.

[0048] In this example, EBNK is Example 1, EBN is Comparative Example 1, EK is Comparative Example 2, E is Comparative Example 3, EBK is Comparative Example 4, ENK is Comparative Example 5, EBN-10K is Comparative Example 6, EBN-20K is Comparative Example 7, EBNK-12 is Comparative Example 8, and EBNK-18 is Comparative Example 9. Detailed Implementation

[0049] This invention provides a method for preparing a vesicle-like porous carbon active anode material, comprising the following steps:

[0050] Tetrasodium ethylenediaminetetraacetate, boron source, nitrate and solvent were mixed and then freeze-dried and carbonized sequentially to obtain a vesicular porous carbon active anode material.

[0051] In this invention, the boron source is preferably ammonium borate.

[0052] In this invention, the nitrate is preferably potassium nitrate, and the solvent is preferably water.

[0053] In this invention, tetrasodium ethylenediaminetetraacetate serves as the nitrogen, oxygen, and carbon source for the vesicular porous carbon active negative electrode material.

[0054] In this invention, the molar ratio of the tetrasodium ethylenediaminetetraacetate, the boron source, and the nitrate is preferably 1:2.2-3.8:1-2, more preferably 1:2.5-3.5:1.2-1.8, and even more preferably 1:3:1.4-1.5. The volume-to-mass ratio of the solvent to the tetrasodium ethylenediaminetetraacetate is preferably 100-300 mL:1.5-5.5 g, more preferably 150-250 mL:1.9-4.5 g, and even more preferably 200 mL:2.5-3.5 g.

[0055] In this invention, the mixing is preferably carried out under stirring conditions, the mixing rate is preferably 200-800 r / min, more preferably 300-700 r / min, more preferably 400-600 r / min, and the mixing time is preferably 6-15 h, more preferably 7-13 h, and more preferably 10-12 h.

[0056] In this invention, the freeze-drying temperature is preferably -60 to -50°C, more preferably -58 to -52°C, and even more preferably -56 to -55°C; the freeze-drying time is preferably 48 to 64 hours, more preferably 50 to 60 hours, and even more preferably 52 to 55 hours.

[0057] In this invention, the carbonization is preferably carried out in a protective gas atmosphere, preferably argon and / or nitrogen, and the flow rate of the protective gas is preferably 40-100 mL / min, more preferably 50-80 mL / min, and even more preferably 60-70 mL / min; the carbonization temperature is preferably 800-1200℃, more preferably 900-1100℃, and even more preferably 1000℃; the carbonization time is preferably 1-5 h, more preferably 2-4.5 h, and even more preferably 3-4 h; the heating rate to the carbonization temperature is preferably 4-8℃ / min, more preferably 5-7℃ / min, and even more preferably 6℃ / min.

[0058] This invention proposes for the first time a solid-state synthesis method utilizing a liquid template with synergistic combustion activation to prepare vesicular porous carbon active anode materials. First, ethylenediaminetetraacetic acid tetrasodium, ammonium borate, and potassium nitrate self-assemble into a uniformly mixed sponge-like precursor under stirring and freeze-drying conditions. Second, the precursor is carbonized in an inert atmosphere, while ammonium borate reacts with potassium nitrate to generate liquid spherical B2O3, thus forming a liquid template. Furthermore, the concept of "combustion activation" is proposed by utilizing the combustion synthesis reaction between nitrate and ethylenediaminetetraacetic acid tetrasodium in the nitrogen source, as well as the reaction between the combustion synthesis products CO2 and H2O and ethylenediaminetetraacetic acid tetrasodium derivatives. Third, heteroatoms are successfully introduced by utilizing the reactions of the generated NO2, NH3, O2, and B2O3 with ethylenediaminetetraacetic acid tetrasodium derivatives, successfully synthesizing a nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material.

[0059] In this invention, after carbonization is completed, the carbonization product is post-processed to obtain a vesicle-like porous carbon active negative electrode material. The post-processing preferably includes sequential removal of impurities, separation, washing, and drying.

[0060] In this invention, the preferred method for impurity removal is to place the carbonized product in water and stir it to wash away the impurities; the preferred temperature for impurity removal is 15–40°C, more preferably 25–30°C; the preferred method for separation is vacuum filtration; the preferred washing reagent is water, and the preferred number of washings is 2–4 times, more preferably 3 times; the preferred drying temperature is 70–120°C, more preferably 80–110°C, more preferably 90–100°C; the preferred drying time is 8–30 hours, more preferably 12–25 hours, more preferably 15–20 hours.

[0061] The present invention also provides a vesicle-like porous carbon active anode material prepared by the preparation method described above.

[0062] The present invention also provides the application of the aforementioned vesicular porous carbon active anode material in sodium-ion batteries.

[0063] In this invention, the assembly of the sodium-ion battery includes the following steps:

[0064] After mixing vesicular porous carbon active negative electrode material, conductive agent and binder, N-methylpyrrolidone is added and mixed thoroughly. The resulting mixture is then evenly dropped onto a stainless steel sheet and dried to form a negative electrode sheet. In an argon-filled glove box, the negative electrode sheet, glass fiber separator and sodium metal disc are assembled into a sodium-ion battery.

[0065] In this invention, the conductive agent is preferably Li-90, and the binder is preferably polyvinylidene fluoride; the mass ratio of the vesicular porous carbon active negative electrode material, the conductive agent, and the binder is preferably 7-8.5:1-2:1, more preferably 7.5-8.0:1.5:1; the volume ratio of N-methylpyrrolidone to the binder is preferably 1:1.3-2, more preferably 1:1.5-1.7, and more preferably 1:1.6; the thickness of the mixture dropped onto the stainless steel sheet is preferably 50-400 μm, more preferably 60-350 μm, and more preferably 100-210 μm; the drying temperature is preferably 60-90℃, and more preferably 70-80℃.

[0066] In this invention, the electrolyte of the sodium-ion battery is preferably an ether-based electrolyte or an ester-based electrolyte, and the concentration of the electrolyte is preferably 1-1.3 mol / L, more preferably 1.1-1.2 mol / L; the ether-based electrolyte uses sodium bis(fluorosulfonyl)imide (NaFSI) as the solute and diethylene glycol dimethyl ether as the solvent; the ester-based electrolyte uses sodium bis(fluorosulfonyl)imide (NaFSI) as the solute and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 as the solvent.

[0067] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0068] The glass fiber diaphragm is Whatman GF / D glass fiber filter paper 1823-047.

[0069] Example 1

[0070] (1) Preparation of nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBNK):

[0071] 5 mmol of tetrasodium ethylenediaminetetraacetate, 15 mmol of ammonium borate, and 6 mmol of potassium nitrate were completely dissolved in 200 mL of deionized water and stirred at 400 rpm for 6 h. The mixture was then freeze-dried at -55 °C for 50 h. Subsequently, the dried mixture was carbonized by heating to 1000 °C at a rate of 5 °C / min under a nitrogen atmosphere (N2 flow rate of 60 mL / min) and holding at that temperature for 2 h. The carbonized product was washed with water at 30 °C to remove impurities, then filtered under a vacuum of 0.098 MPa, washed three times with deionized water, and finally dried at 100 °C for 15 h to obtain porous carbon, denoted as boron-nitrogen-oxygen-triple-doped vesicular porous carbon active anode material (EBNK).

[0072] (2) Assembly of sodium-ion batteries:

[0073] A boron-nitrogen-oxygen-oxide-boron triple-doped vesicular porous carbon active anode material (EBNK), conductive agent Li-90, and polyvinylidene fluoride were mixed at a mass ratio of 7.5:1.5:1, and then added to N-methylpyrrolidone (N-methylpyrrolidone to polyvinylidene fluoride volume ratio of 1:1.6) and mixed thoroughly. The resulting mixture was then uniformly dropped onto a stainless steel sheet (the thickness of the mixture was 210 μm) and dried in an oven at 70 °C to obtain the anode sheet. The anode sheet, glass fiber separator, and sodium metal disc were assembled into a sodium-ion battery in an argon-filled glove box. Two sodium-ion batteries were assembled according to the above method, with ether-based electrolyte and ester-based electrolyte, respectively, and all other aspects being the same. The ether-based electrolyte has a concentration of 1 mol / L, with sodium difluorosulfonamide as the solute and diethylene glycol dimethyl ether as the solvent; the ester-based electrolyte has a concentration of 1 mol / L, with sodium difluorosulfonamide as the solute and ethylene carbonate and diethyl carbonate (volume ratio 1:1) as the solvent.

[0074] Example 2

[0075] (1) Preparation of nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBNK):

[0076] 10 mmol of tetrasodium ethylenediaminetetraacetate, 35 mmol of ammonium borate, and 15 mmol of potassium nitrate were completely dissolved in 250 mL of deionized water and stirred at 600 rpm for 10 h. The mixture was then freeze-dried at -58 °C for 55 h. Subsequently, the dried mixture was carbonized by heating to 800 °C at a rate of 7 °C / min under a nitrogen atmosphere (N2 flow rate of 80 mL / min) and holding at that temperature for 4 h. The carbonized product was washed with water at 25 °C to remove impurities, then separated by filtration under a vacuum of 0.098 MPa, washed twice with deionized water, and then dried at 80 °C for 20 h to obtain porous carbon, denoted as boron-nitrogen-oxygen-triple-doped vesicular porous carbon active anode material (EBNK).

[0077] (2) Assembly of sodium-ion batteries:

[0078] The obtained boron-nitrogen-oxygen-oxygen-coated vesicular porous carbon active anode material (EBNK), conductive agent Li-90, and polyvinylidene fluoride were mixed at a mass ratio of 8.0:1.5:1, and then added to N-methylpyrrolidone (the volume ratio of N-methylpyrrolidone to polyvinylidene fluoride was 1:1.5) and mixed thoroughly. The resulting mixture was uniformly dropped onto a stainless steel sheet (the thickness of the mixture was 100 μm), and then dried in an oven at 80 °C to obtain the anode sheet. The anode sheet, glass fiber separator, and sodium metal disc were assembled into a sodium-ion battery in an argon-filled glove box. Two sodium-ion batteries were assembled according to the above method. The electrolytes of these two sodium-ion batteries were ether-based electrolyte and ester-based electrolyte, respectively, and all other aspects were the same. The ether-based electrolyte has a concentration of 1.2 mol / L, with sodium difluorosulfonamide as the solute and diethylene glycol dimethyl ether as the solvent; the ester-based electrolyte has a concentration of 1.2 mol / L, with sodium difluorosulfonamide as the solute and ethylene carbonate and diethyl carbonate (volume ratio 1:1) as the solvent.

[0079] Comparative Example 1

[0080] (1) Nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBN)

[0081] The difference from Example 1 is that no activator potassium nitrate is added.

[0082] (2) Assembly of sodium-ion batteries:

[0083] The difference from Example 1 is that the boron-nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBNK) is replaced with boron-nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBN), otherwise it is the same as Example 1.

[0084] Comparative Example 2

[0085] (1) Nitrogen-oxygen-doped porous carbon active anode material (EK)

[0086] The difference from Example 1 is that no boron source, ammonium borate, is added.

[0087] (2) Assembly of sodium-ion batteries:

[0088] The difference from Example 1 is that the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBNK) is replaced with nitrogen-oxygen-doped porous carbon active anode material (EK), otherwise it is the same as Example 1.

[0089] Comparative Example 3

[0090] (1) Nitrogen-oxygen doped porous carbon active anode material (E)

[0091] The difference from Example 1 is that no boron source ammonium borate and activator potassium nitrate are added.

[0092] (2) Assembly of sodium-ion batteries:

[0093] The difference from Example 1 is that the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBNK) is replaced with nitrogen-oxygen-doped porous carbon active anode material (E), otherwise it is the same as Example 1.

[0094] Comparative Example 4

[0095] (1) Nitrogen-oxygen-boron triple-doped porous carbon active anode material (EBK)

[0096] The difference from Example 1 is that sodium tetraborate is used instead of ammonium borate as the boron source.

[0097] (2) Assembly of sodium-ion batteries:

[0098] The difference from Example 1 is that the boron-oxygen-nitrogen triple-doped vesicular porous carbon active anode material (EBNK) is replaced with boron-oxygen-nitrogen triple-doped porous carbon active anode material (EBK), otherwise it is the same as Example 1.

[0099] Comparative Example 5

[0100] (1) Nitrogen-oxygen-doped porous carbon active anode material (ENK)

[0101] The difference from Example 1 is that there is no boron source, and ammonium chloride is used instead of ammonium borate.

[0102] (2) Assembly of sodium-ion batteries:

[0103] The difference from Example 1 is that the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBNK) is replaced with nitrogen-oxygen-doped porous carbon active anode material (ENK), otherwise it is the same as Example 1.

[0104] Comparative Example 6

[0105] (1) Nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBN-10K)

[0106] The difference from Example 1 is that the amount of ammonium borate added is slightly lower than that of EBNK, and the amount of ammonium borate is 10 mmol.

[0107] (2) Assembly of sodium-ion batteries:

[0108] The difference from Example 1 is that the boron-nitrogen triple-doped vesicular porous carbon active anode material (EBNK) is replaced with boron-nitrogen triple-doped vesicular porous carbon active anode material (EBN-10K), otherwise it is the same as Example 1.

[0109] Comparative Example 7

[0110] (1) Nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBN-20K)

[0111] The difference from Example 1 is that the amount of ammonium borate added is slightly higher than that of EBNK, and the amount of ammonium borate is 20 mmol.

[0112] (2) Assembly of sodium-ion batteries:

[0113] The difference from Example 1 is that the boron-nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBNK) is replaced with boron-nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBN-20K), otherwise it is the same as Example 1.

[0114] Comparative Example 8

[0115] (1) Nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBNK-12)

[0116] The difference from Example 1 is that the amount of potassium nitrate activator added is slightly higher than that of EBNK, and the amount of potassium nitrate is 12 mmol.

[0117] (2) Assembly of sodium-ion batteries:

[0118] The difference from Example 1 is that the boron-oxygen-nitrogen triple-doped vesicular porous carbon active anode material (EBNK) is replaced with boron-oxygen-nitrogen triple-doped vesicular porous carbon active anode material (EBNK-12), otherwise it is the same as Example 1.

[0119] Comparative Example 9

[0120] (1) Nitrogen-oxygen-boron triple-doped porous carbon active anode material (EBNK-18)

[0121] The difference from Example 1 is that the amount of potassium nitrate activator added is much higher than that of EBNK, with potassium nitrate being 18 mmol.

[0122] (2) Assembly of sodium-ion batteries:

[0123] The difference from Example 1 is that the boron-nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBNK) is replaced with boron-nitrogen-oxygen-boron triple-doped porous carbon active anode material (EBNK-18), otherwise it is the same as Example 1.

[0124] The morphology and properties of the porous carbon active anode materials obtained in Example 1 and Comparative Examples 1-9 were tested, and the results are as follows: Figures 1-12 The results are shown in Table 1. The morphology and structure of the porous carbon active anode material were observed using scanning electron microscopy (SEM); the phase composition of the porous carbon active anode material was determined by X-ray diffraction; and the specific surface area and pore volume of the porous carbon active anode material were tested by nitrogen adsorption-desorption at 77K (specifically, nitrogen was used as the adsorption medium, and helium and hydrogen were used as carrier gases; the helium and hydrogen were mixed at a volume ratio of 4:1 and adjusted to a predetermined relative pressure level (0–0.1, 0.1–0.8, 0.8–1.0) to allow the mixed gas to... The solid sample to be tested was flowed through (45 mL / min). When the sample tube was placed in liquid nitrogen to maintain -100°C, the solid sample began to physically adsorb nitrogen from the mixed gas, while the carrier gas molecules did not participate in the adsorption. As the liquid nitrogen was removed, the sample tube returned to room temperature, at which point the previously adsorbed nitrogen began to desorb. By comparing the areas of the correction peak and the desorption peak, the amount of adsorption of the sample at a given relative pressure could be calculated. X-ray photoelectron spectroscopy (XPS) was used to characterize the elemental content of the porous carbon active anode material.

[0125] SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBNK) in Example 1 is shown below. Figure 1 As shown. By Figure 1 As can be seen, the EBNK of Example 1 is a hierarchical porous structure composed of stacked vesicular shells. As shown in Table 1, the EBNK of Example 1 has a hierarchical porous structure, vesicular shell morphology, and three types of heteroatom doping, which is beneficial to enhance the wettability of the electrolyte, shorten the ion diffusion distance, promote ion insertion or extraction, and provide abundant active sites for charge transfer reactions.

[0126] SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBN) of Comparative Example 1 is shown below. Figure 2 As shown. By Figure 2 It can be seen that the EBN of Comparative Example 1 has a mixed structure of vesicular spherical shells and bulk materials. As shown in Table 1, the EBN of Comparative Example 1 has a porous structure and three types of heteroatom doping, which is beneficial to enhance the wettability of the electrolyte, shorten the ion diffusion distance, promote the insertion or extraction of ions, and provide abundant active sites for charge transfer reactions.

[0127] SEM image of the nitrogen-oxygen-doped porous carbon active anode material (EK) of Comparative Example 2 is shown below. Figure 3As shown. By Figure 3 It can be seen that the EK in Comparative Example 2 is a randomly stacked fragment structure. As shown in Table 1, the EK in Comparative Example 2 has a porous structure and two types of heteroatom doping, which is beneficial to enhance the wettability of the electrolyte, shorten the ion diffusion distance, promote the insertion or extraction of ions, and provide abundant active sites for charge transfer reactions.

[0128] SEM image of nitrogen-oxygen doped porous carbon active anode material (E) of Comparative Example 3 is shown below. Figure 4 As shown. By Figure 4 It can be seen that E in Comparative Example 3 is a randomly stacked fragment structure. As shown in Table 1, E in Comparative Example 3 has a porous structure and two types of heteroatom doping, which is beneficial to enhance the wettability of the electrolyte, shorten the ion diffusion distance, promote the insertion or extraction of ions, and provide abundant active sites for charge transfer reactions.

[0129] SEM image of the nitrogen-oxygen-boron triple-doped porous carbon active anode material (EBK) of Comparative Example 4 is shown below. Figure 5 As shown. By Figure 5 It can be seen that EBK in Comparative Example 4 has a bulk structure, indicating that the boron oxide template obtained from the reaction of ammonium borate and nitrate has a significant impact on the control of material morphology. Only when a spherical boron oxide template is formed can a vesicle-like morphology be formed. As shown in Table 1, EBK in Comparative Example 4 has a porous structure and three types of heteroatom doping, which is beneficial for enhancing the wettability of the electrolyte, shortening the ion diffusion distance, promoting ion insertion or extraction, and providing abundant active sites for charge transfer reactions.

[0130] SEM image of nitrogen-oxygen doped porous carbon active anode material (ENK) of Comparative Example 5 is shown below. Figure 6 As shown. By Figure 6 It can be seen that the ENK in Comparative Example 5 has a bulk structure, indicating that the boron oxide template obtained from the reaction of ammonium borate and nitrate has a significant impact on the control of material morphology. Only when a spherical boron oxide template is formed can a vesicle-like morphology be formed. As shown in Table 1, the ENK in Comparative Example 5 has a porous structure and two types of heteroatom doping, which is beneficial to enhancing the wettability of the electrolyte, shortening the ion diffusion distance, promoting ion insertion or extraction, and providing abundant active sites for charge transfer reactions.

[0131] SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBN-10K) of Comparative Example 6 is shown below. Figure 7 As shown. By Figure 7It can be seen that EBN-10K in Comparative Example 6 exhibits a structure where vesicular spherical shells and bulk structures coexist. This indicates that the boron oxide template obtained from the reaction of ammonium borate and nitrate has a significant impact on the control of material morphology. When the amount of ammonium borate added is small, some bulk structures will exist. As shown in Table 1, EBN-10K in Comparative Example 6 has a porous structure and three types of heteroatom doping, which is beneficial for enhancing the wettability of the electrolyte, shortening the ion diffusion distance, promoting ion insertion or extraction, and providing abundant active sites for charge transfer reactions.

[0132] SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBN-20K) of Comparative Example 7 is shown below. Figure 8 As shown. By Figure 8 It can be seen that EBN-20K in Comparative Example 7 has a vesicular shell structure, but some of the vesicular shells are not open, indicating that the boron oxide template obtained from the reaction of ammonium borate and nitrate has an important influence on the control of material morphology. When the amount of ammonium borate added is too large, the reaction between ammonium borate and the activator nitrate will be insufficient, resulting in an unopened vesicular shell structure. As shown in Table 1, EBN-20K in Comparative Example 7 has a porous structure and three types of heteroatom doping, which is beneficial to enhancing the wettability of the electrolyte, shortening the ion diffusion distance, promoting ion insertion or extraction, and providing abundant active sites for charge transfer reactions.

[0133] SEM image of the nitrogen, oxygen, and boron triple-doped vesicular porous carbon active anode material (EBNK-12) of Comparative Example 8 is shown below. Figure 9 As shown. By Figure 9 It can be seen that EBNK-12 in Comparative Example 8 has a structure of vesicular shells and disordered fragments stacked together, indicating that the boron oxide template obtained from the reaction of ammonium borate and nitrate has an important influence on the control of material morphology. When the amount of nitrate activator added is large, the continuous open-pore vesicular shell structure is severely destroyed, resulting in the appearance of disordered fragment structure. As shown in Table 1, EBNK-12 in Comparative Example 8 has a porous structure and three types of heteroatom doping, which is beneficial to enhance the wettability of electrolyte, shorten the ion diffusion distance, promote ion insertion or extraction, and provide abundant active sites for charge transfer reactions.

[0134] SEM image of the nitrogen, oxygen, and boron triple-doped porous carbon active anode material (EBNK-18) of Comparative Example 9 is shown below. Figure 10 As shown. By Figure 10It can be seen that EBNK-18 in Comparative Example 9 exhibits a disordered, fragmented stacked structure, indicating that the boron oxide template obtained from the reaction of ammonium borate and nitrate has a significant impact on the control of material morphology. When the amount of nitrate activator added is excessive, the continuously open-celled vesicular shell structure is severely damaged, leading to the disappearance of the vesicular shell structure and the appearance of a disordered fragmented structure. Table 1 shows that EBNK-18 in Comparative Example 9 has a porous structure and three types of heteroatom doping, which is beneficial for enhancing the wettability of the electrolyte, shortening the ion diffusion distance, promoting ion insertion or extraction, and providing abundant active sites for charge transfer reactions.

[0135] X-ray diffraction patterns of the porous carbon active anode materials obtained in Examples 1 and 3 are shown below. Figure 11 As shown, the X-ray diffraction patterns of the porous carbon active anode materials obtained in Comparative Examples 4-9 are as follows: Figure 12 As shown.

[0136] Performance tests were conducted on the two sodium-ion batteries assembled in Example 1 and Comparative Examples 1-9. The test methods were as follows: Cyclic voltammetry, constant current charge-discharge curves, rate performance, and electrochemical impedance spectroscopy were performed on the assembled sodium-ion batteries at room temperature using a Chenhua CHI660E electrochemical workstation and a Xinwei CT-4008T. The test results are as follows: Figures 13-23 As shown in Table 1.

[0137] The rate performance comparison diagrams of the porous carbon active anode materials obtained in Examples 1 and 3 (Comparative Examples 1-3) as anodes in ether-based electrolytes are shown below. Figure 15 As shown, the impedance comparison diagrams of the porous carbon active anode materials obtained in Examples 1 and Comparative Examples 1-3 as anodes in sodium-ion batteries in ether-based electrolytes are as follows. Figure 17 As shown in the figure, the rate performance comparison of the porous carbon active anode materials obtained in Comparative Examples 4-9 as anodes in sodium-ion batteries in ether-based electrolytes is as follows. Figure 16 As shown in the figure, the impedance comparison diagrams of the porous carbon active anode materials obtained in Comparative Examples 4-9 as anodes in sodium-ion batteries in ether-based electrolytes are as follows. Figure 18 As shown, EBNK is Example 1, EBN is Comparative Example 1, EK is Comparative Example 2, E is Comparative Example 3, EBK is Comparative Example 4, ENK is Comparative Example 5, EBN-10K is Comparative Example 6, EBN-20K is Comparative Example 7, EBNK-12 is Comparative Example 8, and EBNK-18 is Comparative Example 9; Figure 17 and Figure 18It can be seen that the charge transfer impedance (Rct) of the negative electrodes of EBNK, EBN, EK, E, EBK, ENK, EBN-10K, EBN-20K, EBNK-12, and EBNK-18 are 9.4Ω, 9.3Ω, 22.7Ω, 11.0Ω, 11.1Ω, 16.8Ω, 9.4Ω, 27.0Ω, 13.6Ω, and 15.6Ω, respectively. The relatively small Rct of EBNK in Example 1 indicates that its hybrid network structure composed of alternating disordered and ordered regions is beneficial to improving Na... + Transport dynamics.

[0138] The specific capacity and cycling performance of EBNK in Example 1 under ether-based electrolyte and different currents are as follows: Figure 19 As shown. By Figure 19 It is evident that EBNK exhibits outstanding rate performance in ether-based electrolytes: at 0.5 A / g, 5 A / g, 10 A / g, 20 A / g, 30 A / g, 40 A / g, and 50 A / g, it provides 355.0 mAh / g, 290.0 mAh / g, 252.7 mAh / g, 205.6 mAh / g, 175.0 mAh / g, 155.6 mAh / g, and 175.0 mAh / g, respectively.

[0139] A specific capacity of 125.0 mAh / g and excellent cycle life: after 5500 cycles at 20 A / g, it exhibits a specific capacity of 138.9 mAh / g. These results demonstrate that the hybrid network structure of the boron-nitrogen-oxygen-coated vesicular porous carbon active anode material (EBNK), composed of alternating disordered and ordered regions, achieves a balance between high conductivity and high electrochemical activity, enabling it to exhibit ultrafast Na+ cycling at high current densities. + Storage kinetics and ultra-high structural stability result in superior rate performance and cycle life.

[0140] The higher resistivity of the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBN) in Comparative Example 1 indicates that the presence of bulk structures, compared to continuous vesicular shell structures, slows down the ion diffusion rate, increases the energy barrier for ion migration, and reduces ion diffusion kinetics. The bulk stacked structure has a larger ion migration energy barrier than the interconnected vesicular shell structure; the disorder of the conductive network leads to reduced conductivity, thus hindering the diffusion rate of ions and electrons, ultimately resulting in the inferior electrochemical performance of EBN compared to EBNK. The higher resistivity of the nitrogen-oxygen-doped porous carbon active anode material (EK) in Comparative Example 2 and the higher resistivity of the nitrogen-oxygen-doped porous carbon active anode material (E) in Comparative Example 3 indicate that the randomly stacked fragmented structure, compared to continuous vesicular shell structures, significantly slows down the ion diffusion rate, increases the energy barrier for ion migration, and reduces ion diffusion kinetics. Randomly stacked fragmented structures, compared to interconnected vesicular shell structures, exhibit larger ion migration barriers and longer ion diffusion channels. Furthermore, the disorder of the conductive network leads to reduced conductivity, thus hindering the diffusion rates of ions and electrons. Ultimately, this results in the electrochemical performance of EK and E being inferior to that of EBNK. The high resistivity of the nitrogen-oxygen-boron triple-doped porous carbon active anode material (EBK) in Comparative Example 4, the nitrogen-oxygen-doped porous carbon active anode material (ENK) in Comparative Example 5, and the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBN-10K) in Comparative Example 6 all indicate that bulk structures, compared to continuous vesicular shell structures, significantly slow down the ion diffusion rate, increase the ion migration barrier, and reduce ion diffusion kinetics. Compared to interconnected vesicular spherical structures, bulk structures have larger ion migration barriers and longer ion diffusion channels. Furthermore, the disorder of the conductive network leads to a decrease in conductivity, which hinders the diffusion rate of ions and electrons. Ultimately, this results in the electrochemical performance of EBK, ENK, and EBN-10K being inferior to that of EBNK.

[0141] The higher resistivity of the boron-nitrogen-oxygen-phosphate triple-doped vesicular porous carbon active anode material (EBN-20K) in Comparative Example 7 indicates that the unopened vesicular shell structure, compared to a continuously open vesicular shell structure, slows down the ion diffusion rate, increases the energy barrier for ion migration, and reduces ion diffusion kinetics. The unopened vesicular shell structure, compared to a continuously open vesicular shell structure, has a larger ion migration energy barrier, a longer ion diffusion channel, and the disorder of the conductive network leads to reduced conductivity, thus hindering the diffusion rate of ions and electrons, ultimately resulting in the inferior electrochemical performance of EBN-20K compared to EBNK. The higher resistivity of the boron-nitrogen-oxygen-phosphate triple-doped vesicular porous carbon active anode material (EBNK-12) in Comparative Example 8 indicates that the partial disruption of the vesicular shell structure, compared to a continuously open vesicular shell structure, slows down the ion diffusion rate, increases the energy barrier for ion migration, and reduces ion diffusion kinetics. Compared to continuously open vesicular shell structures, the fragmented vesicular shell structure exhibits a larger ion migration barrier and a longer ion diffusion channel. Furthermore, the disorder of the conductive network reduces conductivity, thus hindering the diffusion rates of ions and electrons. Ultimately, this results in EBNK-12 exhibiting inferior electrochemical performance compared to EBNK. The higher resistivity of the nitrogen-oxygen-boron triple-doped porous carbon active anode material (EBNK-18) in Comparative Example 9 indicates that the disordered fragment stacking structure formed by the disruption of the vesicular shell structure, compared to continuously open vesicular shell structures, slows down the ion diffusion rate, increases the ion migration barrier, and reduces ion diffusion kinetics. The disordered fragment stacking structure, compared to continuously open vesicular shell structures, exhibits a larger ion migration barrier and a longer ion diffusion channel. Furthermore, the disorder of the conductive network reduces conductivity, thus hindering the diffusion rates of ions and electrons. Ultimately, this results in EBNK-18 exhibiting inferior electrochemical performance compared to EBNK.

[0142] The charge-discharge curves of the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material obtained in Example 1 as a sodium-ion battery anode in ether-based and ester-based electrolytes at a current density of 0.05 A / g are shown in the figure below. Figure 20 As shown. By Figure 20As shown in Table 1, the ICE (interval between ionization and electrochemical conductivity) of the boron-nitrogen-oxygen-oxide-doped vesicular porous carbon active anode material (EBNK) in ether-based and ester-based electrolytes are 96.5% and 21.3%, respectively, indicating that more active sodium participates in the electrochemical process in the ether-based electrolyte. In the ether-based electrolyte, EBNK provides specific capacities of 487.5 mAh / g and 296.1 mAh / g at 0.05 A / g and 2 A / g, respectively. In the ester-based electrolyte, EBNK provides specific capacities of 316.7 mAh / g and 133.9 mAh / g at 0.05 A / g and 2 A / g, respectively. At 0.05 A / g and 2 A / g, the specific capacity of EBNK decreases steadily in the ether-based electrolyte, while it decreases sharply in the ester-based electrolyte. These performance results demonstrate that EBNK can maintain excellent sodium activity in both ether-based and ester-based electrolytes. + Storage kinetics. Furthermore, EBNK exhibits optimal Na content in ether-based electrolytes. + Storage kinetics. The reversible capacities of EBNK, EBN, EK, E, EBK, ENK, EBN-10K, EBN-20K, EBNK-12, and EBNK-18 at 0.05 A / g were 487.5 mAh / g, 348.0 mAh / g, 307.6 mAh / g, 293.9 mAh / g, 299.2 mAh / g, 335.4 mAh / g, 354.9 mAh / g, 363.0 mAh / g, 329.3 mAh / g, and 310.7 mAh / g, respectively, with corresponding ICE values ​​of 96.5%, 85.2%, 74.5%, 71.5%, 67.5%, 69.7%, 67.3%, 77.7%, 72.8%, and 70.3%. The EBNK anode exhibits the highest reversible capacity and ICE (internal conductivity). This is because its vesicular spherical morphology, hierarchical porous structure, and heteroatom doping increase the contact area with the electrolyte and accelerate the electron-naphthalene exchange. + This improves the transmission rate and enhances the wettability of the electrode material.

[0143] The cyclic voltammetry curves of the nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material obtained in Example 1 as the anode of a sodium-ion battery in ether-based or ester-based electrolytes at 0.2 mV / s are shown below. Figure 22 and Figure 23 As shown. By Figure 22 and Figure 23It can be seen that the boron-nitrogen-oxygen-boron triple-doped vesicular porous carbon active anode material (EBNK) exhibits different redox peaks in its CV curve at 0.2 mV / s in either ether-based or ester-based electrolytes. In the ether-based electrolyte, the anodic peaks of EBNK in the first CV curve are located at 1.16 V and 2.19 V, while the cathode peaks are at 0.53 V and 0.01 V, which differs from the cathode peaks (0.32 V and 0.01 V) and anodic peaks (1.47 V and 2.52 V) in the ester-based electrolyte. This indicates that the sodium storage process of the boron-nitrogen-oxygen-boron triple-doped vesicular porous carbon anode material (EBNK) differs in the two electrolytes (e.g., the formation of the SEI layer, Na...). + Storage kinetics / mechanisms, stability of metallic Na). The cathode peak near 0.01V on the CV curve represents Na. + Embedded between carbon layers or Na + Filling the pores, other cathode peaks represent electrolyte decomposition, SEI layer formation, or Na+. + It is trapped by defects. Furthermore, compared to ester-based electrolytes, EBNK exhibits a smaller first-cycle CV curve area in ether-based electrolytes, indicating a higher ICE (internal efficiency) in ether-based electrolytes. In both electrolytes, the second and third-cycle CV curves of EBNK almost overlap, demonstrating EBNK's excellent stability.

[0144] Table 1. Performance of porous carbon active anode materials as anodes in Examples 1 and Comparative Examples 1-9.

[0145]

[0146] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a vesicle-like porous carbon active anode material, characterized in that, It includes the following steps: Tetrasodium ethylenediaminetetraacetate, boron source, nitrate and solvent were mixed and then freeze-dried and carbonized sequentially to obtain a vesicular porous carbon active anode material.

2. The preparation method according to claim 1, characterized in that, The boron source is ammonium borate.

3. The preparation method according to claim 1 or 2, characterized in that, The nitrate is potassium nitrate, and the solvent is water.

4. The preparation method according to claim 2, characterized in that, The molar ratio of the ethylenediaminetetraacetic acid tetrasodium, boron source, and nitrate is 1:2.2-3.8:1-2, and the volume-to-mass ratio of the solvent to ethylenediaminetetraacetic acid tetrasodium is 100-300 mL:1.5-5.5 g.

5. The preparation method according to claim 4, characterized in that, The mixing is carried out under stirring conditions, with a mixing rate of 200–800 r / min and a mixing time of 6–15 h.

6. The preparation method according to claim 4 or 5, characterized in that, The freeze-drying temperature is -60 to -50°C, and the freeze-drying time is 48 to 64 hours.

7. The preparation method according to claim 6, characterized in that, The carbonization is carried out in a protective gas atmosphere, the protective gas being argon and / or nitrogen, with a flow rate of 40–100 mL / min; the carbonization temperature is 800–1200 °C, the carbonization time is 1–5 h, and the heating rate to the carbonization temperature is 4–8 °C / min.

8. The preparation method according to claim 7, characterized in that, After carbonization, the carbonization product is post-processed to obtain a vesicular porous carbon active anode material. The post-processing includes sequential removal of impurities, separation, washing, and drying. The drying temperature is 70-120℃.

9. The vesicle-like porous carbon active anode material prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the vesicular porous carbon active negative electrode material according to claim 9 in sodium-ion batteries.